2013
DOI: 10.4028/www.scientific.net/msf.773-774.242
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Solder Bond on Thermal Mismatch Stresses in Electronic Packaging Assembly

Abstract: Thermo-mechanical stresses have been considered one of the major concerns in electronic Packaging assembly structural failure. The interfacial stresses are often caused by the thermal mismatch stresses induced by the coefficient of thermal expansion (CTE) difference between materials, typically during the high temperature change in the bonding process. This research work examined the effect of bond layer on thermal mismatch interfacial stresses in a bi-layered assembly. The paper verified the existing thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…(12) it can be observed that when gradient in materials is zero (∆T 1 =∆T 3 ) and (∆T 2 =∆T 4 ), the term A 2 becomes zero and eq. (10) and (11) reduces to (7) and (8), which are the differential uniform temperature model. It is also observed that the correction factor A 2 (in eq.…”
Section: Bi-materials Linear Temperature Gradient Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) it can be observed that when gradient in materials is zero (∆T 1 =∆T 3 ) and (∆T 2 =∆T 4 ), the term A 2 becomes zero and eq. (10) and (11) reduces to (7) and (8), which are the differential uniform temperature model. It is also observed that the correction factor A 2 (in eq.…”
Section: Bi-materials Linear Temperature Gradient Modelmentioning
confidence: 99%
“…As a result, a generalized form of the bi-material model is required to be constructed which should be able to take care of any temperature condition in the layers. The effect of heat generation on interfacial stresses due to the presence of a heat source in a layer is also needs to be investigated [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately this induced thermo-mechanical mismatch stress is one of the main causes of mechanical and functional failure in electronic and photonic devices. As the power requirement of the devices increases, the problem with thermal mismatch assumes a major cause of failure in electronic packages [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Suhir showed that for relatively small assemblies, compliant attachment could indeed result in substantial stress relief in both the adherents and the adhesives. Sujan proposed a model for shearing and peeling stresses at the interface of bi-material assembly which satisfies the interface compatibility by matching of strains at the interface rather than the actual displacements as in Suhir's work [1,6,[13][14][15]. As a consequence, an unnecessary integro-differential equation was avoided by solving only a simpler second order differential equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation